Training on the Development of Utilization of Digital Teaching Materials for Teachers to Improve Student Learning Outcomes - Kadarisman; Marisa; Asnah M.N. Limbung; Suryo Prabowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
In the era of the industrial revolution 4.0, modern technology such as fibre technology and integrated network systems in all aspects of life has made humans very dependent on technology. The purpose of this research is to foster a culture of digital literacy in the school environment, increase teacher knowledge and skills in the field of developing and utilizing digital teaching materials, improve student learning performance and increase teacher knowledge and skills in terms of digital learning models and improve student's learning performance. The method used in this study is the observation method using the pre-experimental design method, one group type pretest-posttest (pretest test-posttest single group). Assistance was provided to 28 junior high school teachers in the South Tangerang area. During the training, participants were given four assignments: Team, Sway, Learning Design and Learning Videos. The study results show that as many as 71% of teachers have mastered the Teams and Sway applications from Microsoft, 60% can make lesson plans, and 53% can make learning videos. The pretest and post-test results showed that the average result was 36.6%, then after participating in the training, the average result was 44.4%. The results of the study show that training in the development and use of digital teaching materials has an effect on the skills and abilities of teachers, which is beneficial for improving student learning performance.